Iconics: Icon Evolution in Digitality - Steven John Thompson (tripleC: Communication, Capitalism & Critique)
Image manipulation, archiving, and sharing are all critical technological aspects of Western culture and postmodern civilization. Consequently, creation, identification, dissemination, and proliferation of powerful images across media channels today indicate a burgeoning area of information technology.